Perspektif Masyarakat Terhadap Suku Togutil, Halmahera Timur, Maluku Utara - Eksa Agustamanda; Nurjanah Nurjanah; Yufira Amilia (Pusat Riset dan Inovasi Nasional, 2024)
The Togutil tribe is one of the inland tribes and also a community group that widely inhabits forests in the East Halmahera region. The Togutil tribe is a group of indigenous people who live in the Halmahera region, North Maluku. This community is known for its nomadic lifestyle and dependence on forests to meet their daily needs. However, social and economic developments as well as interactions with outside society began to change their lifestyle and culture. This research is a qualitative approach using descriptive methods. Research analyzes data from various sources such as journals, articles and other literature. It is hoped that this research will be able to explain how the surrounding community, including local non-Togutil residents, local governments and other community groups view the Togutil Tribe. This includes their perceptions of culture, customs and lifestyle as well as the community's views on the Togutil tribe.